2020
DOI: 10.1038/s41598-020-70459-3
|View full text |Cite
|
Sign up to set email alerts
|

Electrical antimicrobial susceptibility testing based on aptamer-functionalized capacitance sensor array for clinical isolates

Abstract: capacitance changes. As a result, bacterial activities, such as growth and death, can be monitored in real-time by measuring the capacitance change, allowing more rapid AST 23,24. For AST of clinical samples, it is necessary to simultaneously test various antimicrobial agents at different concentrations; therefore, we fabricated sensor arrays consisting of 60 sensors. Among the 60 sensors, two and three sensors were used for negative and positive controls, respectively, and the other 55 sensors were used to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Growth of cells is monitored by detecting capacitance change of bacteria bound to 60 aptamer-functionalized capacitance sensors [46] Mechanical-based AST methods…”
Section: Electric Resistancementioning
confidence: 99%
“…Growth of cells is monitored by detecting capacitance change of bacteria bound to 60 aptamer-functionalized capacitance sensors [46] Mechanical-based AST methods…”
Section: Electric Resistancementioning
confidence: 99%
“…Patients' survival could be highly improved if they received timely and effective antibiotic treatment, but antimicrobial susceptibility test (AST) results usually require more than three days with conventional methods [80][81][82]. In addition to the quantitative and qualitative detection of bacteria, the aptamer sensor can monitor the real-time growth of bacteria and biofilm, which continuously and timely evaluate the internal infections and the effectiveness of antibiotics [46,47]. For instance, Song et al developed a vertical capacitance aptamer-functionalized sensor (Fig.…”
Section: Real-time Monitoring Of Bacterial Growth and Astmentioning
confidence: 99%
“…This study demonstrated that an aptamer-functionalized sensor could be used as an alternative tool for detecting bacteria and rapid AST in positive blood culture without the need for sub-culturing. Furthermore, Lee et al developed an electrical AST (e-AST) system, which shortens the AST time to only 6 h [47]. The e-AST system was composed of 60 aptamerfunctionalized capacitance sensors, of which 2 sensors were used for the negative control, 3 sensors for positive control, and other 55 sensors for the determination of antibiotic sensitivity to 11 antibiotics at 5 different concentrations.…”
Section: Real-time Monitoring Of Bacterial Growth and Astmentioning
confidence: 99%
“…Susceptibility results were available in <90 min. Lee et al (2020) reported on electrical antimicrobial susceptibility testing based on aptamer‐functionalized capacitance sensor array. Results were reported within 6 h. The electrical AST (e‐AST) is based on an array of 60 aptamer‐functionalized capacitance sensors, and the susceptibility comparisons were with broth microdilution.…”
Section: Introductionmentioning
confidence: 99%